Preparation method of conductive toughened self-lubricating polyimide composite material
By building a carbon material network in polyimide resin, physical assembly and chemical modification using graphene oxide, carbon nanotubes and graphite, the polyimide resin has solved the accumulation of electrostatic charge and low heat resistance at high temperatures. The problem is that the preparation of conductive toughened self-lubricating composite materials is realized, and the conductivity, toughening and self-lubricating properties of the materials are improved.
Patent Information
- Application Number
- CN202411606399.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
During the processing and use of existing polyimide resins, the accumulation of electrostatic charge, the thermal decomposition temperature is close to the limit but the heat resistance is low, and the material is prone to oxidation at high temperatures, resulting in performance attenuation.
By constructing a carbon material network, graphene oxide, carbon nanotubes and graphite are used to physically assemble and chemically modify in polyimide resins to form a conductive toughened self-lubricating composite material. The method includes ultrasonic dispersion, mechanical stirring, frozen block formation and molding processes to improve the conductivity, toughness and self-lubricity of the material.
The conductive and self-lubricating properties of polyimide composites have been improved, which reduces the risks of electrostatic charge accumulation and thermal oxygen aging, and improves the heat and friction properties of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hybrid multi-scale nano composite materials, and in particular relates to a method for preparing a conductive toughened self-lubricating polyimide composite material. Background Art
[0002] The reliability and stability of solid self-lubricating materials have become the key to ensuring the safe and efficient operation of mechanical equipment. Among them, high-temperature self-lubricating polymer-based composite materials have been widely used in aircraft engines, rocket engine near-hot end bearings and mechanical transmission control systems, showing unique advantages in improving thrust-to-weight ratio, corrosion resistance, fatigue resistance and maintenance-free performance. The thermal decomposition temperature range of polyimide is 500-600℃. It has the advantages of high-temperature self-lubricating and good dimensional stability. It is the preferred polymer matrix material for near-hot end wear-resistant parts in the aerospace field.
[0003] However, the existing polyimide resin has the following deficiencies during processing and use: (1) The accumulation of static charge is very serious. In some cases, it will not only affect the performance of the material, but also cause harm. (2) The thermal decomposition temperature of polyimide is close to the theoretical limit of organic polymer materials, but the heat resistance of its composite material is still lower than expected. The fundamental reason is that under high temperature / dry friction conditions, cracks occur in the polymer matrix and debonding occurs at the interface of the composite material, resulting in the intrusion and diffusion of oxidizing media, which leads to performance degradation caused by thermal oxidation aging and structural damage. Under the action of thermal-mechanical coupling, the interaction between polymer chains is weakened, and the polymer matrix undergoes viscoelastic deformation, which reduces the bonding strength between the friction transfer film and the counter-wear surface, resulting in a decrease in friction and wear performance.
[0004] In terms of improving the mechanical properties and electrical conductivity of high-temperature self-lubricating polymer-based composites, metal particles, graphite, chopped carbon fibers, molybdenum disulfide, zinc sulfide, hexagonal boron nitride and other lubricants are compounded with polyimide resin matrix, which not only plays a role in bearing and reducing deformation, but also improves the adhesion strength of the transfer film, reduces the friction coefficient, and improves high-temperature wear resistance. Using metal particles and conductive carbon materials to construct a three-dimensional interconnected network inside the polymer matrix is an effective means to achieve conductivity, toughening and self-lubrication of composite materials. Chinese invention patent CN115785528A discloses MXene@molybdenum disulfide-carbon nanofiber hybrid aerogel and epoxy resin-based composite materials and preparation methods, wherein a MXene@molybdenum disulfide-carbon nanofiber hybrid aerogel / epoxy resin-based composite material is constructed, and the MXene@molybdenum disulfide hybrid includes MXene thin layer nanosheets and molybdenum disulfide grown on the surface of MXene thin layer nanosheets. Hybrid aerogel can avoid the agglomeration of fillers in epoxy resin, and can build an effective heat-conducting network inside the resin and provide skeleton support, thereby improving the load-bearing capacity of epoxy resin and inhibiting the accumulation of frictional heat at the interface. However, molybdenum disulfide begins to oxidize into molybdenum trioxide particles at 200°C, which expands as the temperature rises, increasing friction and causing a decrease in lubrication performance. Chinese invention patent CN101698746A discloses a method for preparing a conductive polyimide film, which uses metal powder and carbon powder as mixed conductive fillers, with a total filler content of 5wt% to 50wt%. Such a high content of fillers will greatly damage the inherent properties of the polyimide matrix, especially flexibility. Chinese invention patent CN103627011A discloses a method for preparing a conductive polyimide composite film. The method uses graphene oxide as a conductor and prepares a graphene / polyimide composite solution by an in-situ polymerization method. The in-situ polymerization method has a narrow scope of application and cannot be used to process commercial polyimides available on the market. In addition, although graphene has good conductivity, the mechanical properties of the film prepared with graphene as a conductor are poor due to the lack of active functional groups on the surface. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a conductive toughened self-lubricating polyimide composite material and a preparation method thereof. By constructing a carbon material network for electron, phonon and load transfer and loading a high-temperature resistant self-lubricating material, the orderly assembly of functional materials of different scales and effective control of their morphological structure are achieved.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0008] (1) ultrasonically dispersing graphene oxide in an aprotic organic solvent to obtain a graphene oxide dispersion;
[0009] (2) adding carbon nanotubes and graphite to the graphene oxide dispersion at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion;
[0010] (3) adding diisocyanate to the three-component dispersion system and mechanically stirring at room temperature for 15 to 25 minutes to obtain a modified three-component dispersion system;
[0011] (4) ball-milling a polyimide resin in an aprotic organic solvent and then adding a cationic surfactant to obtain a polyimide slurry;
[0012] (5) mixing the modified three-component dispersion system and the polyimide slurry, mechanically stirring for 8 hours, and then keeping the mixture at -28°C to -40°C for 120 to 150 minutes to obtain a frozen block;
[0013] (6) placing the frozen block obtained in step (5) in acetone, controlling the temperature to the melting point of the aprotic organic solvent used, soaking for 5 to 7 hours, washing with deionized water to obtain a sponge-like porous polyimide composite material, and obtaining a conductive toughened self-lubricating polyimide composite material through a molding process.
[0014] Furthermore, in step (1), the diameter of the graphene oxide is 20 μm to 80 μm, and the concentration of the graphene oxide dispersion is 1 mg / ml to 10 mg / ml.
[0015] Furthermore, the carbon nanotubes in step (2) are multi-walled carbon nanotubes with unmodified surfaces, an outer diameter of 10 nm to 20 nm, an inner diameter of 5 nm, a length not exceeding 20 μm, and a graphite diameter not exceeding 10 μm.
[0016] Furthermore, the mass ratio of the carbon nanotubes in step (2) to the graphene oxide in step (1) is 10:1 to 6:1, and the mass ratio of the carbon nanotubes to graphite is 1:1.
[0017] Furthermore, the diisocyanate in step (3) is hexamethylene diisocyanate or diphenylmethane diisocyanate, and the mass ratio of diisocyanate to graphene oxide is 1:100 to 2:100.
[0018] Furthermore, the diameter of the polyimide particles after ball milling in step (4) is 1 μm to 2 μm.
[0019] Furthermore, in step (4), the cationic surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride, and the mass ratio of the cationic surfactant to the polyimide resin is 1:100 to 2:100.
[0020] Furthermore, the mass ratio of polyimide to graphene oxide in the frozen block in step (5) is 100:1 to 100:1.5.
[0021] Furthermore, in step (6), the volume ratio of the frozen block to acetone is 1:2 to 1:3, and the molding process parameters are 385°C / 150MPa / 4 hours.
[0022] Furthermore, the aprotic organic solvent in steps (1) and (4) is N-methyl-2-pyrrolidone or N,N-dimethylacetamide, and the aprotic organic solvent in steps (1) and (4) is the same.
[0023] The ultrasonic operating frequency in steps (1) and (2) is 45kHz and the power is 30W.
[0024] Compared with the prior art, the present invention has at least the following advantages and beneficial effects:
[0025] (1) The present invention utilizes the amphiphilicity of graphene oxide to achieve effective control of the morphological structure of conductive carbon nanotubes and self-lubricating graphite in polyimide resin through physical assembly and chemical modification. In the subsequent heating and pressurizing process, the thermally reduced graphene oxide and the graphite as a lubricant synergistically improve the conductive properties and self-lubricating properties of the polyimide composite material.
[0026] (2) The present invention preferably uses unmodified carbon nanotubes as conductive materials, providing a method for efficiently constructing a three-dimensional continuous carbon network inside a polymer matrix, thereby improving the electrostatic dissipation capability of the composite material.
[0027] (3) The method for preparing a heat-conductive and friction-resistant nanocomposite material provided by the present invention is suitable for a thermoplastic polymer matrix with excellent physical properties but high melt viscosity, and realizes the control of the morphological structure, dispersion and distribution of different nanomaterials.
[0028] (4) The preparation method of the present invention is simple, highly operable, low-cost, and easy to mass-produce industrially. It is suitable for preparing polymer-based composite materials used in friction parts such as aerospace, new energy vehicles, electronics and microelectronics. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The reagents or instruments used without indicating the manufacturer are all conventional commercial products.
[0030] The present invention will be further described below in conjunction with specific embodiments.
[0031] Example 1
[0032] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0033] (1) dispersing graphene oxide in N-methyl-2-pyrrolidone by ultrasonication at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0034] (2) adding carbon nanotubes with an outer diameter of 20 nm, an inner diameter of 5 nm, and a length of 2 μm and graphite with a diameter of 10 μm to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion, with an ultrasonic operating frequency of 45 kHz and a power of 30 W;
[0035] (3) adding hexamethylene diisocyanate to the three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of hexamethylene diisocyanate to graphene oxide is 1:100;
[0036] (4) ball-milling a polyimide resin in N-methyl-2-pyrrolidone to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium bromide to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium bromide to polyimide is 1:100;
[0037] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -40°C for 120 minutes to obtain a frozen block;
[0038] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:2), the temperature was controlled to be -24°C, and after soaking for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, and after heating at 385°C and pressurizing at 150 MPa for 4 hours, a conductive toughened self-lubricating polyimide composite material was obtained, and the electrical conductivity was 1.7×10 -2 S / m, and the friction coefficient is 0.18.
[0039] Example 2
[0040] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0041] (1) dispersing graphene oxide in N,N-dimethylacetamide by ultrasonic operation at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0042] (2) adding the carbon nanotubes and graphite described in Example 1 to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion, wherein the ultrasonic operating frequency is 45 kHz and the power is 30 W;
[0043] (3) adding diphenylmethane diisocyanate to the modified three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of diphenylmethane diisocyanate to graphene oxide is 2:100;
[0044] (4) ball-milling a polyimide resin in N,N-dimethylacetamide to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium chloride to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium chloride to polyimide is 2:100;
[0045] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -28°C for 120 minutes to obtain a frozen block;
[0046] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:3), the temperature was controlled at -20°C, and after immersion for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, which was heated at 385°C and pressurized at 150 MPa for 4 hours to obtain a conductive toughened self-lubricating polyimide composite material, and the electrical conductivity was 1.2×10 -2 S / m, and the friction coefficient is 0.15.
[0047] Example 3
[0048] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0049] (1) dispersing graphene oxide in N-methyl-2-pyrrolidone by ultrasonication at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0050] (2) adding the carbon nanotubes and graphite described in Example 1 to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion, wherein the ultrasonic operating frequency is 45 kHz and the power is 30 W;
[0051] (3) adding diphenylmethane diisocyanate to the modified three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of diphenylmethane diisocyanate to graphene oxide is 2:100;
[0052] (4) ball-milling a polyimide resin in N-methyl-2-pyrrolidone to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium bromide to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium bromide to polyimide is 2:100;
[0053] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -40°C for 120 minutes to obtain a frozen block;
[0054] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:3), the temperature was controlled at -24 ° C, and after immersion for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, and after heating at 385 ° C and pressurizing at 150 MPa for 4 hours, a conductive toughened self-lubricating polyimide composite material was obtained, and the electrical conductivity was 1.5×10 -2 S / m, and the friction coefficient is 0.13.
[0055] Example 4
[0056] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0057] (1) dispersing graphene oxide in N,N-dimethylacetamide by ultrasonic operation at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0058] (2) adding the carbon nanotubes and graphite described in Example 1 to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion at an ultrasonic operating frequency of 45 kHz and a power of 30 W;
[0059] (3) adding hexamethylene diisocyanate to the modified three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of hexamethylene diisocyanate to graphene oxide is 2:100;
[0060] (4) ball-milling a polyimide resin in N,N-dimethylacetamide to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium chloride to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium chloride to polyimide is 2:100;
[0061] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -28°C for 120 minutes to obtain a frozen block;
[0062] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:3), the temperature was controlled at -20°C, and after soaking for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, which was heated at 385°C and pressurized at 150 MPa for 4 hours to obtain a conductive toughened self-lubricating polyimide composite material, and the electrical conductivity was 1.1×10 -2 S / m, and the friction coefficient is 0.18.
[0063] Example 5
[0064] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0065] (1) dispersing graphene oxide in N-methyl-2-pyrrolidone by ultrasonication at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0066] (2) adding the carbon nanotubes and graphite described in Example 1 to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion at an ultrasonic operating frequency of 45 kHz and a power of 30 W;
[0067] (3) adding hexamethylene diisocyanate to the modified three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of hexamethylene diisocyanate to graphene oxide is 2:100;
[0068] (4) ball-milling a polyimide resin in N,N-dimethylacetamide to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium chloride to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium chloride to polyimide is 1:100;
[0069] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -40°C for 120 minutes to obtain a frozen block;
[0070] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:2), the temperature was controlled at -24 ° C, and after soaking for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, and after heating at 385 ° C and pressurizing at 150 MPa for 4 hours, a conductive toughened self-lubricating polyimide composite material was obtained, and the electrical conductivity was 1.7×10 -2 S / m, and the friction coefficient is 0.21.
[0071] Example 6
[0072] A method for preparing a conductive toughened self-lubricating polyimide composite material comprises the following steps:
[0073] (1) dispersing graphene oxide in N,N-dimethylacetamide by ultrasonic operation at a frequency of 45 kHz and a power of 30 W to obtain a graphene oxide dispersion;
[0074] (2) adding the carbon nanotubes and graphite described in Example 1 to the dispersion obtained in step (1) at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion at an ultrasonic operating frequency of 45 kHz and a power of 30 W;
[0075] (3) adding diphenylmethane diisocyanate to the modified three-component dispersion system of step (2), stirring at room temperature for 20 minutes to obtain a modified three-component dispersion system, wherein the mass ratio of diphenylmethane diisocyanate to graphene oxide is 2:100;
[0076] (4) ball-milling a polyimide resin in N,N-dimethylacetamide to an average diameter of 1-3 μm, and then adding hexadecyltrimethylammonium bromide to obtain a polyimide slurry, wherein the mass ratio of hexadecyltrimethylammonium bromide to polyimide is 1:100;
[0077] (5) mixing the modified three-component dispersion system obtained in step (3) and step (4) with the polyimide slurry, mechanically stirring for 8 hours, and freezing at -28°C for 120 minutes to obtain a frozen block;
[0078] (6) The frozen block obtained in step (5) was placed in acetone (volume ratio of 1:3), the temperature was controlled at -20°C, and after soaking for 6 hours, it was washed with deionized water to obtain a sponge-like porous polyimide composite material, which was heated at 385°C and pressurized at 150 MPa for 4 hours to obtain a conductive toughened self-lubricating polyimide composite material, and the electrical conductivity was 1.4×10 -2 S / m, and the friction coefficient is 0.22.
Claims
1. A method for preparing a conductive toughened self-lubricating polyimide composite material, characterized in that: The following steps are involved: (1) ultrasonically dispersing graphene oxide in an aprotic organic solvent to obtain a graphene oxide dispersion; (2) adding carbon nanotubes and graphite to the graphene oxide dispersion at the same time, and obtaining a three-component dispersion system after ultrasonic dispersion; (3) adding diisocyanate to the three-component dispersion system and mechanically stirring at room temperature for 15 to 25 minutes to obtain a modified three-component dispersion system; (4) ball-milling a polyimide resin in an aprotic organic solvent and then adding a cationic surfactant to obtain a polyimide slurry; (5) mixing the modified three-component dispersion system and the polyimide slurry, mechanically stirring for 8 hours, and then keeping the mixture at -28°C to -40°C for 120 to 150 minutes to obtain a frozen block; (6) placing the frozen block obtained in step (5) in acetone, controlling the temperature to the melting point of the aprotic organic solvent used, soaking for 5 to 7 hours, washing with deionized water to obtain a sponge-like porous polyimide composite material, and obtaining a conductive toughened self-lubricating polyimide composite material through a molding process.
2. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The diameter of the graphene oxide in step (1) is 20 μm to 80 μm, and the concentration of the graphene oxide dispersion is 1 mg / ml to 10 mg / ml.
3. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The carbon nanotubes in step (2) are multi-walled carbon nanotubes with unmodified surfaces, an outer diameter of 10 nm to 20 nm, an inner diameter of 5 nm, a length not exceeding 20 μm, and a graphite diameter not exceeding 10 μm.
4. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The mass ratio of the carbon nanotubes in step (2) to the graphene oxide in step (1) is 10:1 to 6:1, and the mass ratio of the carbon nanotubes to graphite is 1:
1.
5. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The diisocyanate in step (3) is hexamethylene diisocyanate or diphenylmethane diisocyanate, and the mass ratio of diisocyanate to graphene oxide is 1:100 to 2:
100.
6. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The diameter of the polyimide particles after ball milling in step (4) is 1 μm to 2 μm.
7. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The cationic surfactant in step (4) is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride, and the mass ratio of the cationic surfactant to the polyimide resin is 1:100 to 2:
100.
8. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The mass ratio of polyimide to graphene oxide in the frozen block in step (5) is 100:1 to 100:1.
5.
9. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: In step (6), the volume ratio of the frozen block to acetone is 1:2 to 1:3, and the molding process parameters are 385° C. / 150 MPa / 4 hours.
10. The method for preparing a conductive toughened self-lubricating polyimide composite material according to claim 1, characterized in that: The aprotic organic solvent in steps (1) and (4) is N-methyl-2-pyrrolidone or N,N-dimethylacetamide, and the aprotic organic solvent in steps (1) and (4) is the same.
Citation Information
Patent Citations
Preparation method of electric-conduction polyimide film
CN101698746A
Preparation method of conductive polyimide composite film
CN103627011A
MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel, epoxy resin-based composite material and preparation method of MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel and epoxy resin-based composite material
CN115785528A
Cited By
High-wear-resistance spiral cable for robot and preparation method of high-wear-resistance spiral cable
CN120261036A
Flexible anti-static high-temperature-resistant FDC special film and preparation method thereof
CN120310258A